Stable Correlated 4d2 SrMoO3 Films Epitaxially Coated on Al2O3 for Electromagnetic Shielding and Transparent Conductors. Issue 31 (14th September 2022) - Ha, Youngkyoung; Lee, Shinbuhm
Abstract: Correlated perovskites have attracted significant attention worldwide for their potential application in transparent conductors. However, most studies in this area have focused on single‐crystalline films grown on expensive perovskites. In this study, the transparent conducting properties of SrMoO3 epitaxial films grown on Al2 O3, the most commonly used substrate for optoelectronics, are investigated. The 45−80‐nm‐thick SrMoO3 epitaxial films on ( 1 1 ¯ 02 ) ${\bf (}1\bar{1}02{\bf )}$ ‐oriented Al2 O3 exhibit low sheet resistance (< 50 Ω □ −1 ) at room temperature and high ultraviolet‐visible transmittances (> 60%), comparable with the values expected from single‐crystalline films. The highly conductive properties induced by two electrons in the outermost 4d orbitals guarantee a high electromagnetic shielding effectiveness of approximately 28.5 dB at 10 GHz in the X‐band. The SrMoO3 films are thermally stable below 450 °C in air and 700 °C in vacuum. Taken together, these results indicate that SrMoO3 epitaxial films grown on ( 1 1 ¯ 02 ) \[{\bf (}1\bar{1}02{\bf )}\] Al2 O3 can be highly promising for optoelectronic applications in extreme environments. Abstract : Correlated 4d 2 SrMoO3 films epitaxially coated on Al2 O3 are potential candidates for optoelectronic applications in extreme environments. These films exhibit low sheet resistance (<50 Ω □ −1 ) at room temperature, high transmittance (>60%) in the ultraviolet‐visible spectra, and high electromagnetic shielding effectiveness (approximately 28.5 dB) at 10 GHz in the X‐band. The properties persist below 450 °C in air and even at 700 °C in vacuum.